Anna Freeman Bentley - Mobility and grandeur - Price, Matt (Anomie, 2015)
Anna Freeman Bentley (b. Freeman, 1982) is a painter based in London. Her practice explores the built environment, architecture, and interiors, inviting emotive, psychological, and semiotic readings of space. This, the artist's first monograph, features over forty paintings spanning her career to date
Keywords: Freeman Bentley, Anna -- 1982-; Geschichte 2009-2014; Malerei; Bildband